2011
DOI: 10.1158/0008-5472.can-10-1728
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RNA Polymerase I with an Oral Small Molecule CX-5461 Inhibits Ribosomal RNA Synthesis and Solid Tumor Growth

Abstract: Deregulated ribosomal RNA synthesis is associated with uncontrolled cancer cell proliferation. RNA polymerase (Pol) I, the multiprotein complex that synthesizes rRNA, is activated widely in cancer. Thus, selective inhibitors of Pol I may offer a general therapeutic strategy to block cancer cell proliferation. Coupling medicinal chemistry efforts to tandem cell-and molecular-based screening led to the design of CX-5461, a potent small-molecule inhibitor of rRNA synthesis in cancer cells. CX-5461 selectively inh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
552
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 519 publications
(597 citation statements)
references
References 38 publications
(45 reference statements)
30
552
3
3
Order By: Relevance
“…30 Incubation of organoids with 1 μM CX-5461 resulted in a rapid reduction in rRNA precursors levels ( Figure 6a). After 1 day of treatment, buds size appeared reduced compared with vehicle-treated control organoids (Figure 6b), and after 2 days most treated organoids started to degenerate (not shown).…”
Section: Resultsmentioning
confidence: 98%
“…30 Incubation of organoids with 1 μM CX-5461 resulted in a rapid reduction in rRNA precursors levels ( Figure 6a). After 1 day of treatment, buds size appeared reduced compared with vehicle-treated control organoids (Figure 6b), and after 2 days most treated organoids started to degenerate (not shown).…”
Section: Resultsmentioning
confidence: 98%
“…15 To expand our options of route of administration, we assessed the antitumor activity of 7c, administered ip, in a murine MV 4;11 xenograft model. Once daily, ip administration of 7c resulted in a dose-dependent inhibition of tumor growth (Figure 2).…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…For this purpose, we developed and deployed a cell-based qRT-PCR assay that measures the differential effects of new chemical entity (NCE) on Pol I-and Pol II-driven transcription, as previously described. 15 The in vitro antiproliferative activity of analogues was evaluated using colorectal adenocarcinoma HCT-116 cells and then expanded to additional cell lines. To rapidly screen compounds for oral absorption, a cassette format 16,17 was used to dose ICR mice at 25 mg/kg for each compound, and blood was collected at 0.25, 0.5, 1, 2, 4, 6, and 8 h. These efforts led to the rapid discovery of 2-(4-methyl- [1,4]diazepan-1-yl)-5-oxo-5H-7-thia-1,11b-diaza-benzo[c]-fluorene-6-carboxylic acid (5-methyl-pyrazin-2-ylmethyl)-amide (CX-5461, 7c), a highly potent, selective, and specific inhibitor of rRNA synthesis that suppresses Pol I transcription at the initiation stage and exhibits antiproliferative activity in vitro and antitumor activity in xenograft models.…”
mentioning
confidence: 99%
“…Recent study showed that the RNA Pol I inhibitor CX5461 is an efficient inducer of senescence. 16 Knockdown of NML also reduced the efficiency of CX5461-induced senescence based on the SA-b-gal marker staining ( Fig. 1E) and colony formation assay (data not shown).…”
Section: Depletion Of Nml Reduces the Efficiency Of Senescence Responsementioning
confidence: 83%
“…Recently the RNA Pol Ispecific inhibitor CX5461 has shown promise as an anti-tumor agent in animal models, in part by activating p53 through the nucleolar stress signaling mechanism that inhibits MDM2 function. 16,17 Nearly 50% of rDNA repeats are present as heterochromatin in growing cells, which is important for maintaining genetic stability. 18 The NoRC (nucleolar remodeling complex) is important for switching rDNA between silent and active state.…”
Section: Introductionmentioning
confidence: 99%